Traumatic events and suicidal behavior in the Nigerian survey of mental health and well-being (2012)
Objective: Not much is known about the role of different traumatic events in predicting suicidal outcomes. We investigated the association of specific traumatic events with different suicidal outcomes. Method: Data are from the Nigerian Survey of Mental Health and Well-Being, a multistage probability household survey of persons aged 18 years and over. Information on traumatic events and suicidal behaviours (ideation, plan and attempts) was collected in face-to-face interviews using the Composite International Diagnostic Interview (CIDI.3) from a subsample of the respondents (N = 2143). Results: At least one traumatic event was reported by 63% of the sample. Traumatic events were more likely to have been experienced by individuals with different suicidal outcomes, with a dose–response relationship between the number of traumatic events and suicide ideation. The risks of suicidal ideation were elevated among persons with a history of combat experience (OR 6.3 95% CI 1.8–21.8) and those with exposure to war (OR 4.2; 95% CI 1.6–10.6), while that of suicidal attempt was increased among persons with experience of interpersonal violence (OR 4.3; 95% CI 1.4–13.0). Conclusion: Traumatic events are common in the general population. This report highlights the role of traumatic events (especially those related to violence) in predicting suicidal behaviour.